Transnationalism and Chinese diaspora’s struggle for identity in British Malaya (1900- 1957) - Abdillah Noh (Penerbit Universiti Kebangsaan Malaysia, 2022)
Malayan Chinese muted response to the Malayan Union proposal in 1946 which promised common citizenship rights and equal opportunity to non-Malays have not been sufficiently explained by existing literature. This article suggests that such muted response is due to the presence of Chinese transnationalism that diluted and diverted the community’s attention from seeking a Malayan identity. The article provides evidences that the increasing return nature of Chinese transnational politics and the institutionalisation of Chinese transnational linkages made a complete removal of Chinese transnational ties difficult. This article employs a historical institutional analysis, tracing the development and evolution of Chinese transnationalism from the mid nineteenth century to the period of Malaya’s independence. Using tools like process tracing, increasing returns, institutional density and path dependence, it will chronologically piece events throughout the above said period to explain how Chinese transnationalism evolve into a Malayan nationalism as a result of a confluence of factors – Malayan independence, the start of China’s communist rule in 1949 and the integration of Chinese communities within the larger Malayan community. Contrary to existing arguments, Chinese nationalism towards Malaya and Malaysia is a relatively new phenomenon; it had its roots probably in the late 1940s and almost certainly after the 1950s. This work is important because the “migration” from Chinese transnationalism to Chinese nationalism after the 1950s, could help provide clues towards understanding the political construction of modern Malaysian society.